Ultrahigh resolution, serial fabrication of three dimensionally-patterned protein nanostructures by liquid-mediated non-contact scanning probe lithography. Issue 55 (23rd May 2016) - Gan, Tiansheng; Wu, Bo; Zhou, Xuechang; Zhang, Guangzhao
Abstract : Sub-100 nm and 3D-patterned structures of protein are fabricated on Au surface in solution by liquid-mediated non-contact scanning probe lithography. Abstract : To mimic the functionality of the complex surface morphology of living systems, the fabrication of artificial 3D-patterned structures has attracted increasing attention and much progress has been made in recent years. Here, a liquid-mediated non-contact scanning probe lithography method was developed for the serial fabrication of patterned structures of protein. Very importantly, protein structures with different heights were successfully fabricated by precisely controlling the slow scan direction, set point value, and scan pixel density. What is more, sub-100 nm dot and sub-50 nm line arrays of protein structures were fabricated. This method opens up a new path for the rational design of surface-tethered 3D-patterned architectures directly from biomolecules.